AMPELOGRAPHICAL CHARACTERISTICS AND genotypic variability in autochthonous CULTIVARS red and black Valando vo Drenok grown in R. MACEDONIA - Korunoska, B.; Bozinovik, Z.; Sarafimovska, A.; Prculovski, Z.; Nedelkovski, D.; Taseska-Gjorgjijevski, M. (Institute of agriculture, Skopje, 2015)
Ampelographical description is very important for more precise determination of the morphological and physiological characteristics of a certain cultivar or to determine the variability in the cultivar and the existence of some varieties of that cultivar. Cultivars red and black Valandovo drenok are late, table, autochthonous or incurred domestic cultivars of grapevine. Mostly, they are grown in mixed plantings, limited to a small number in the vineyard region in R. Macedonia. They can be found as individual vines in yards and small plantings often grown in odrin - system. Also, these two cultivars meet together in the plantations and in combination with other cultivars to act for their pollination (have functionally female flowers). In some literature data are assumed to black Valandovo drenok is variety of red Valandovo drenok. In this paper are presents the results of more annual examinations of the ampelographical characteristics with more detail and accurately in reaching the knowledge of their origin and autochthony, their features and similarity with the ancestors and also getting data for certain genotypic variations in grapevine cultivars and the existence of varieties. In R. Macedonia, these cultivars grown long period of time, but can be found Introduced in other Balkan countries. They have many positive properties that can be used to further selection. The autochthonous cultivars are rich genetic fund of grapevine important to one country.
Keywords: autochthonous cultivars, ampelographical description, variability, genetic fund